2014
DOI: 10.1002/art.38273
|View full text |Cite
|
Sign up to set email alerts
|

Features of the Synovium of Individuals at Risk of Developing Rheumatoid Arthritis: Implications for Understanding Preclinical Rheumatoid Arthritis

Abstract: ObjectiveFindings from previous studies have suggested that subclinical inflammation of the synovium does not coincide with the appearance of rheumatoid arthritis (RA)–specific autoantibodies. This study was undertaken to examine the relationship between the presence of autoantibodies, changes in the synovium, and development of arthritis over time in a markedly larger, prospective study.MethodsFifty-five individuals who were IgM rheumatoid factor positive and/or anti–citrullinated protein antibody (ACPA) posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(128 citation statements)
references
References 39 publications
7
119
0
2
Order By: Relevance
“…The data presented by Air o and colleagues as well as the data derived from our own studies and those from other researchers, show shifts in CD81 T cell populations both in RA patients (6)(7)(8) and related animal models (9-11), and stress their dependence on disease activity and therapeutic strategy. CD81 T cell function and biology are garnering the greater attention of RA researchers, and these lymphocytes may prove to be valuable targets for future therapeutic and diagnostic strategies.…”
Section: Replysupporting
confidence: 58%
“…The data presented by Air o and colleagues as well as the data derived from our own studies and those from other researchers, show shifts in CD81 T cell populations both in RA patients (6)(7)(8) and related animal models (9-11), and stress their dependence on disease activity and therapeutic strategy. CD81 T cell function and biology are garnering the greater attention of RA researchers, and these lymphocytes may prove to be valuable targets for future therapeutic and diagnostic strategies.…”
Section: Replysupporting
confidence: 58%
“…91 A positive ACPA status in those with arthralgia is associated with the subsequent development of arthritis in only about 20-30% of these people after 30 months of follow up. 92,93 The synovial tissue of patients who are at risk of arthritis has also been examined in two relatively small studies Little evidence of synovitis was found in the first and subtle T-cell infiltration was noted in the second. 94 Data on alternative tissues such as lung and lymph node that may be important in the very early stages of arthritis as sites of first antigen presentation.…”
Section: Early Arthritis and Early Diagnosismentioning
confidence: 99%
“…Anti-CCP antibodies and anti-citrullinated filaggrin antibodies are locally produced in inflamed joints; citrullinated fibrin is found in the synovia of patients with RA, and interestingly citrullinated proteins were extracted from lungs of patients with chronic obstructive pulmonary disease [53][54][55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%